2016
DOI: 10.3390/ijms17050693
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CmWRKY10 in Drought Tolerance of Chrysanthemum through the ABA-Signaling Pathway

Abstract: Drought is one of the important abiotic factors that adversely affects plant growth and production. The WRKY transcription factor plays a pivotal role in plant growth and development, as well as in the elevation of many abiotic stresses. Among three major groups of the WRKY family, the group IIe WRKY has been the least studied in floral crops. Here, we report functional aspects of group IIe WRKY member, i.e., CmWRKY10 in chrysanthemum involved in drought tolerance. The transactivation assay showed that CmWRKY1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…The p35S::GFP- CmMYB19 construct and the empty pMDC43 vector were introduced into onion epidermal cells via particle bombardment (PDS-1000; Bio-Rad, Tokyo, Japan). Transformed cells were held for 16 h on Murashige and Skoog (MS) medium in the dark, and then subjected to confocal laser microscopy in order to monitor GFP activity [40]. …”
Section: Methodsmentioning
confidence: 99%
“…The p35S::GFP- CmMYB19 construct and the empty pMDC43 vector were introduced into onion epidermal cells via particle bombardment (PDS-1000; Bio-Rad, Tokyo, Japan). Transformed cells were held for 16 h on Murashige and Skoog (MS) medium in the dark, and then subjected to confocal laser microscopy in order to monitor GFP activity [40]. …”
Section: Methodsmentioning
confidence: 99%
“…Heterologous expression of CmMYB2 enhanced drought tolerance in Arabidopsis thaliana by increasing plant sensitivity to ABA and reducing stomata aperture 17 . Moreover, recent studies have indicated that the CmWRKY10, DgNAC1, and ClCBF1 transcription factors could also improve the level of drought tolerance in C. morifolium [18][19][20] . In addition to the study of gene function, high-throughput sequencing was applied to identify candidate genes in response to drought stress.…”
mentioning
confidence: 99%
“…After two days of drought and salt treatment, the activity levels of SOD, POD and CAT in the leaves were determined by the method described previously [32]. For the determination of Pro (proline) and MDA (malondialdehyde) content, the transgenic lines and the WT were selected one week after exposure to drought/salt stress, as described previously [50].…”
Section: Measurement Of Antioxidant Enzymes Proline and Malondialdehydementioning
confidence: 99%